EVALUASI KUALITAS VISUAL DAN FUNGSIONAL RUMPUT LAPANGAN SEPAKBOLA - E Junathan Muakhor; Nizar Nasullah; Afra DN Makalew (http://arl.faperta.ipb.ac.id/, 2013)
ABSTRACT Soccer is one of the popular sport around the world. Nowaday, Indonesia has more or less 170 soccer fields. Soccer requires fileds with excellent turfgrass which comply quality standards. This study was aimed to evaluate visual and functional qualities of soccer field, and propose recommendations related to management of soccer field that can fulfill visual and functional qualities. This study was conducted at three soccer stadiums namely Gelora Bung Karno Stadium (Jakarta), Si Jalak Harupat Stadium (Bandung), and Maguwoharjo Stadium (Yogyakarta). Survey and sampling methods were used together with interview method. Sampling based on parameter of visual and functional qualities. Then, analyzed by compare the data with standard quality. Planting medium and leaves samples has taken to laboratory analyzed. Grass quality of Maguwoharjo Stadium has the lowest quality than the others because the shortage of fertilizer condition in planting medium. Consequently, it affected grass growth and performance. Bades on the existing problems, some improvements of planting medium fertility were needed to get the optimal growth and performance in Maguwoharjo Stadium, such as adding the lime and compost or zeolit into planting media to increase the soil pH and CEC (Cation Exchange Capacity).Keywords: Fertilizing, mowing, planting medium, soccer grass field, visual and functional qualities